Crystal Method For Accurate Software Duration Estimation - Sobah, Periasamy; Herman, Nanna Suryana (2007)

(untitled)
All projects share one common characteristic that is the projection of ideas and activities into new endeavours. The ever-present element of risk and uncertainty to the events and tasks leading to completion can never be foretold with absolute accuracy. The software projects are different from other projects. Underestimation is the root course of many software projects not being able to meet the deadline, or failure. Some of the reasons for inaccurate estimation are as follows: the traditional model not being able to capture the project in detail, quick and reliable strategic analysis. The influence of human factor is not able to incorporate explicitly. Failure to consider rework phenomenon. Failure to capture dynamic interaction between technical development and management policies.